2022
DOI: 10.1002/lary.30008
|View full text |Cite
|
Sign up to set email alerts
|

Can Imaging Predict Hearing Outcomes in Children With Cochleovestibular Nerve Abnormalities?

Abstract: Objectives/Hypothesis To identify the imaging characteristics associated with better hearing outcomes found in cochleovestibular nerve (CVN) abnormalities treated with hearing aids and/or cochlear implantation (CI). Study Design Retrospective review. Methods A retrospective review was undertaken of 69 ears with CVN abnormalities seen on magnetic resonance imaging (MRI) treated at a tertiary referral academic center analyzing the clinical features, imaging characteristics, and hearing data. We searched for asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…This means that the absence of the CN according to MRI did not always represent the absence of the anatomical CN and that some CN fibers may be present within the vestibular or facial nerve. In our study, the performance of children with CND was not related to the IAM nerve grade, which was based on the MRI findings of nerves within the IAM and the size of the CN; this finding is not in line with those of some reports ( 11 , 12 , 22 ), which concluded that better performance was related to more nerve bundles. The reason for this difference might be the small sample size of these studies, as many were case reports wherein statistical analysis was not conducted.…”
Section: Discussioncontrasting
confidence: 99%
“…This means that the absence of the CN according to MRI did not always represent the absence of the anatomical CN and that some CN fibers may be present within the vestibular or facial nerve. In our study, the performance of children with CND was not related to the IAM nerve grade, which was based on the MRI findings of nerves within the IAM and the size of the CN; this finding is not in line with those of some reports ( 11 , 12 , 22 ), which concluded that better performance was related to more nerve bundles. The reason for this difference might be the small sample size of these studies, as many were case reports wherein statistical analysis was not conducted.…”
Section: Discussioncontrasting
confidence: 99%
“…The quantitative metrics of the fiber density offer an objective alternative to the subjective visual examination of the VIII th nerve relied upon in structural MRI analysis. This could be advantageous as the subjective interpretation of imaging results may vary depending on clinician experience [ 9 ]. Diffusion-weighted MRI has previously been successful in identifying the axonal neuropathy affecting the VIII th nerve in individuals with X-linked auditory neuropathy [ 10 ], where the VIII th nerve fiber density results obtained from affected individuals have been correlated with perceptual ability.…”
Section: Imagingmentioning
confidence: 99%
“…There is an opinion that modern imaging methods cannot accurately reflect the state of the cochlear nerve or predict the benefit of CI for a child [3]. The presence of several anomalies of the temporal bone further complicates the decision to operate.…”
Section: Introductionmentioning
confidence: 99%